Insight into the mechanisms of enhanced retinal transduction by the engineered AAV2 capsid variant ‐7m8. Issue 12 (30th June 2016) - Khabou, Hanen; Desrosiers, Mélissa; Winckler, Céline; Fouquet, Stéphane; Auregan, Gwenaëlle; Bemelmans, Alexis‐Pierre; Sahel, José‐Alain; Dalkara, Deniz
ABSTRACT: Recently, we described a modified AAV2 vector—AAV2‐7m8—having a capsid‐displayed peptide insertion of 10 amino acids with enhanced retinal transduction properties. The insertion of the peptide referred to as 7m8 is responsible for high‐level gene delivery into deep layers of the retina when virus is delivered into the eye's vitreous. Here, we further characterize AAV2‐7m8 mediated gene delivery to neural tissue and investigate the mechanisms by which the inserted peptide provides better transduction away from the injection site. First, in order to understand if the peptide exerts its effect on its own or in conjunction with the neighboring amino acids, we inserted the 7m8 peptide at equivalent positions on three other AAV capsids, AAV5, AAV8, and AAV9, and evaluated its effect on their infectivity. Intravitreal delivery of these peptide insertion vectors revealed that only AAV9 benefited from 7m8 insertion in the context of the retina. We then investigated AAV2‐7m8 and AAV9‐7m8 properties in the brain, to better evaluate the spread and efficacy of viral transduction in view of the peptide insertion. While 7m8 insertion led to higher intensity gene expression, the spread of gene expression remained unchanged compared to the parental serotypes. Our results indicate that the 7m8 peptide insertion acts by increasing efficacy of cellular entry, with little effect on the spread of viral particles in neural tissue. The effects of peptide insertion are capsid and tissue dependent, highlighting the importance of the microenvironment in gene delivery using AAV. Biotechnol. Bioeng. 2016;113: 2712–2724. © 2016 Wiley Periodicals, Inc. Abstract : The authors recently described AAV2‐7m8, a vector that outperforms other vectors described for retinal transduction of mouse and primate retina. It is characterized by the insertion of a 10‐amino acid peptide referred to as 7m8. Here, Khabou and coworkers provide insight into the mechanisms for its enhanced gene delivery properties. They used in vitro and in vivo analyses to demonstrate increased cell entry of the particles and enhanced infectivity in transduced cells and tissues, both resulting in higher transgene expression levels.